(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
ultimedia plays a crucial role in English language teaching and learning, offering a multitude of benefits, with one of the most significant being the enhancement of listening and speaking skills through audio and video materials. By incorporating multimedia resources like podcasts, videos, and audio recordings, educators can facilitate learners’ exposure to authentic language usage and provide them with ample opportunities to practice listening and speaking across various contexts. multimedia not only elevates listening and speaking abilities but also aids in a deeper comprehension of the culture embedded within the target language. Furthermore, a more a positive correlation between students’ speaking proficiency and their engagement with multimedia devices. This underscores the pivotal role multimedia resources play in language instruction, as they make the learning experience more immersive and engaging, ultimately resulting in improved language proficiency. In essence, multimedia empowers both educators and learners to harness the full potential of language learning, bridging the gap between theoretical knowledge and practical communication skills.